Viral dynamics and patterns of lysogeny in Antarctic saline lakes - Laybourn-Parry, J; Marshall, WA; Madan, NJ (Polar Biology, 2007)
Antarctic lakes are extreme ecosystems with microbially dominated food webs, in which viruses may be important in controlling community dynamics. A year long investigation of two Antarctic saline lakes (Ace and Pendant Lakes) revealed high concentrations of virus like particles (VLP) (0.20-1.26 108 ml-1), high VLP: bacteria ratios (maximum 70.6) and a seasonal pattern of lysogeny differing from that seen at lower latitudes. Highest rates of lysogeny (up to 32% in Pendant Lake and 71% in Ace Lake) occurred in winter and spring, with low or no lysogeny in summer. Rates of virus production (range 0.176-0.823 106 viruses ml-1 h-1) were comparable to lower latitude freshwater lakes. In Ace Lake VLP did not correlate with bacterial cell concentration or bacterial production but correlated positively with primary production, while in Pendant Lake VLP abundance correlated positively with both bacterial cell numbers and bacterial production but not with primary production. In terms of virus and bacterial dynamics the two saline Antarctic lakes studied appear distinct from other aquatic ecosystems investigated so far, in having very high viral to bacterial ratios (VBR) and a very high occurrence of lysogeny in winter. 2006 Springer-Verlag.